Transmission properties in Fibonacci quasi-periodic photonic crystal containing negative-zero-positive index metamaterials. (1st March 2023) - Li, Xinyu; Kong, Qian; Wang, Xinglin; Shen, Ming
Abstract: The transmission properties in Fibonacci quasi-periodic photonic crystals containing negative-zero-positive index metamaterials (NZPIM) are investigated systematically. Because of linear dispersion, an asymmetric band gap appears near the optical Dirac point (DP) only at an oblique incidence. Zero- n ¯ gaps and Bragg gaps exist when the refractive indexes of NZPIM are negative and positive, respectively. We also obtain gaps induced by total reflection on both sides of the DP gap. The corresponding Goos-Hänchen (GH) shifts and phase variations are also demonstrated in detail. It is shown that the characteristics of the band gaps, GH shifts, and phase variations depend crucially on the incident angle, number of periods, and layer thickness.